2019
DOI: 10.24034/j25485024.y2018.v2.i4.426
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Etika Bisnis, Faktor Kontingensi Dan Tingkat Penggunaan Internet Terhadap Daya Saing

Abstract: Tujuan jangka panjang dari penelitian ini agar UMKM di Kabupaten Pamekasan secara keseluruhan bisa memiliki Daya Saing yang sangat unggul sehingga bisa lebih dikenal oleh pasar dunia terutama ditingkat MEA. Target khususnya adalah UMKM dengan Daya Saing tinggi bisa meningkatkan  kontribusi PDRB perkapita Kabupaten Pamekasan, volume ekspor serta menjadi instrumen pemerataan pendapatan, mengurangi ketimpangan kesejahteraan masyarakat dan terbukanya lapangan kerja baru. Untuk bisa bersaing di pasar bebas UMKM her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…Customer loyalty (Thaichon et al, 2014 occurs when consumers make purchases on an ongoing basis from time to time and have a good attitude towards retail stores that provide goods or services . Enjoyment, fantasy, emotions and feelings in hedonic shopping values in the modern retail environment (Anderson et al, 2014 andRia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Customer loyalty (Thaichon et al, 2014 occurs when consumers make purchases on an ongoing basis from time to time and have a good attitude towards retail stores that provide goods or services . Enjoyment, fantasy, emotions and feelings in hedonic shopping values in the modern retail environment (Anderson et al, 2014 andRia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, strategi diperlukan untuk meningkatkan daya saing. Ada beberapa faktor yang dapat mempengaruhi daya saing yang pertama adalah Etika Bisnis, yang kedua adalah Faktor Kontingensi dan yang ketiga adalah Penggunaan Teknologi, ketiga faktor tersebut merupakan implementasi yang tepat dalam strategi bisnis perusahaan sebagai salah satu usaha untuk memenangkan persaingan (Zainurrafiqi & Rachmawati, 2019).…”
Section: Pendahuluanunclassified
“…This means that the internet has become a medium for people to find preferences for needs, which are practical for finding information. Looking for information before buying is not a new event in consumer behavior but has become a trend [3], [4].…”
Section: Table 1 the Internet User In Indonesia January 2012-january ...mentioning
confidence: 99%
“…MSMEs play a very crucial role in economic development in Indonesia, this can be seen from the role of MSMEs which greatly contribute to the development of the national economy. MSMEs that have various products with their uniqueness have shown very significant developments in adopting the right strategy to be able to be competitive in the global market [4]. However, in the midst of the current pandemic, it turns out that the trend of sales or e-commerce transactions in Indonesia is number 1, which finally can be concluded that even in limited conditions for access outside the home, customers can still fulfill their needs by utilizing business platforms such as Lazada, Tokopedia, Shopee and others, as well as business people, especially for MSMEs.…”
Section: Table 1 the Internet User In Indonesia January 2012-january ...mentioning
confidence: 99%